The structural relationship of job stress, job satisfaction, organizational commitment, and turnover intention among youth sports education leaders in Korea - Jung, Myung Kyu; Jung, Tae Gyeom; Jeon, Min Woo; Lee, Ji Hae (Frontiers in Psychology, 2024)
This paper is a study aimed at providing insights for developing effective human resource management strategies suitable for Korean youth sports education facilities, by elucidating the multifaceted relationships among job stress, job satisfaction, organizational commitment, and turnover intention. Through the research, it was academically suggested that the relationships among job stress, job satisfaction, organizational commitment, and turnover intention of Korean youth sports education facility workers could be structurally and complementarily manifested. To fulfill this objective, data were gathered using snowball sampling from Sports leaders who have experience or are engaged in sports education facilities for youth in Korea as of 23 years. A total of 384 responses were analyzed using frequency, technical statistics, and confirmatory factor, reliability, correlation, and structural equation model analyses. Results: Through these analyses, this study found that job Stress, job satisfaction, organizational commitment were significant as both direct and indirect influences on turnover Intention. Intervention strategies should focus on fostering the positive emotions that stem from Intermediation, mitigation, and improvement of job stress.